LITERATURE REVIEW: USE OF ESSENTIAL OIL AROMATHERAPY TOWARDS PAIN REDUCTION IN CANCER PATIENTS - Lopulalan, Syaneti; Antia, Antia; Sukarno, Anita; Asmirajanti, Mira (Universitas Islam Negeri Alauddin Makassar, 2021)
Pain is one of the most common symptoms experienced by cancer patients, and as much as 68% of the causes of pain are experienced by cancer patients (primary tumors). Patients with pain should receive the treatment that can provide the greatest benefit in pain management. For this reason, this research was conducted with the aim of; The purpose of this study was to find out the effect of the use of aromatherapy inhalation of essential oils on reducing pain in cancer patients. The method used in this study is to use